ANALISIS TATANIAGA BERAS DARI LUAR BERAU DI KECAMATAN TANJUNG REDEB KABUPATEN BERAU (Analysis of Rice Marketing from Berau Outside in Tanjung Redeb Subdistrict Berau District) - PUTRI AYU ISTIFARI; SUWARNO SUWARNO (Universitas Mulawarman (University of Mulawarman), 2020)
The fulfillment of rice in Berau District comes some in part from paddy yield in that district and partly comes from district outside. This study aimed to know the channels of rice marketing, the marketing margin, and the ratio of profit to costs of rice marketingfrom Berau outside in Tanjung Redeb Subdistrict, Berau District. This research was carried out during 3 months from November 2019 to January 2020 in Tanjung Redeb Subdistrict, Berau District. The sampling method used census and the snowball sampling method with a total of 41 respondents devided into 5 distributors, 6 agents, and 30 retailers. The results of this research showed that rice marketing from Berau outside in Tanjung Redeb Subdistrict uses the marketing channel level one dan two. The biggest margin value is in distributor as much as IDR85,446,033.33. The big profit and cost ratio is in distributor and agent as much as IDR6.25 kg-1 rice.